(untitled) (International Journal of Mathematics and Physics, 2025)
Aaruul is a traditional dairy product from Mongolia, recognized for its nutritional qualities and potential health benefits. Traditionally produced through manual milk processing at home, aaruul is increasingly mass-produced for commercial markets. This study aimed to investigate the effects of X-ray irradiation on Khorkhoi aaruul, a widely consumed small-curd variety. Samples were exposed to irradiation doses of 1 kGy, 3 kGy, and 5 kGy to evaluate reductions in bacterial contamination, extension of shelf life, and compliance with international food safety standards. The changes in vitamin C content and organoleptic properties (taste, texture, and appearance) were systematically assessed. Trace element composition was quantified using Energy-Dispersive X-ray Fluorescence (ED-XRF) spectrometry, focusing on phosphorus (P), calcium (Ca), zinc (Zn), iron (Fe), manganese (Mn), copper (Cu), and bromine (Br). Results indicated a substantial reduction in bacterial counts, achieving a 95.5% decrease at the 5 kGy dose (from 4.2×106 to 2×105 CFU). Critically, irradiation did not induce significant alterations in chemical composition, sensory quality, or vitamin C levels. These findings demonstrate the effectiveness of X-ray irradiation as a viable approach to enhancing microbial safety and prolonging the shelf life of traditional Mongolian dairy products without compromising their nutritional or sensory characteristics. Keywords: Aaruul, irradiation, trace elements, ED-XRF, colony formation unit